Transforaminal lumbar interbody fusion using polyetheretherketone oblique cages with and without a titanium coating: a randomised clinical pilot study. (October 2017) - Rickert, M.; Fleege, C.; Tarhan, T.; Schreiner, S.; Makowski, M. R.; Rauschmann, M.; Arabmotlagh, M.
Abstract : Aims: We compared the clinical and radiological outcomes of using a polyetheretherketone cage with (TiPEEK) and without a titanium coating (PEEK) for instrumented transforaminal lumbar interbody fusion (TLIF). Materials and Methods: We conducted a randomised clinical pilot trial of 40 patients who were scheduled to undergo a TLIF procedure at one or two levels between L2 and L5. The Oswestry disability index (ODI), EuroQoL-5D, and back and leg pain were determined pre-operatively, and at three, six, and 12 months post-operatively. Fusion rates were assessed by thin slice CT at three months and by functional radiography at 12 months. Results: At final follow-up, one patient in each group had been lost to follow-up. Two patients in each of the PEEK and TiPEEK groups were revised for pseudarthrosis (p = 1.00). The rate of complete or partial fusion at three months was 91.7% in both groups. Overall, there were no significant differences in ODI or in radiological outcomes between the groups. Conclusion: Favourable results with identical clinical outcomes and a high rate of fusion was seen in both groups. The titanium coating appears to have no negative effects on outcome or safety in the short term. A future study to determine the effect of titanium coating is warranted. Cite this article: Bone Joint J 2017;99-B:1366–72.